Polar Record: A Journal of Arctic and Antarctic Research - Polar Record: A Journal of Arctic and Antarctic Research (Cambridge University Press, 2026)
Polar Record is a Gold Open Access journal that publishes articles in a wide variety of areas of polar research in both the Arctic and the Antarctic and keeping its readers up to date with an extensive range of topics and concerns. The journal includes original primary research papers in the physical sciences, life sciences, polar technology, humanities, and social sciences, as well as papers concerning current political, economic, legal, and environmental issues. Notes, review papers, book reviews, letters to the editor, guest editorials, obituaries, and ‘In Brief’ items of general interest are also published.
FI 0.3
Q3
Keywords: Earth; Space & Environmental Sciences; Quaternary Science & Glaciology; Ciencia del Cuaternario; Glaciología; Acuerdos transformativos; Transformative agreements; Ártico; Antártida; Ciencias de la vida; Tecnología polar